2007
DOI: 10.1590/s0006-87052007000400009
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros genéticos de caracteres relacionados à tolerância à deficiência hídrica em milho tropical

Abstract: A seleção de caracteres relacionados à tolerância à deficiência hídrica em milho tem sido objeto de interesse em programas de melhoramento, principalmente em virtude da ineficiência da seleção para produzir grãos nessas condições. O objetivo deste trabalho foi estimar parâmetros genéticos em duas populações de milho tropical. Foram avaliadas duas populações (denominadas D e U) com 256 progênies F 2:3 , no delineamento em látice 16 x 16 em sete ou nove ambientes e densidade populacional de 62.500 plantas ha -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
20

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 8 publications
0
19
0
20
Order By: Relevance
“…Ainda segundo esses autores, o oxigênio é também fator fundamental para o processo germinativo, pois participa da degradação das substâncias de reserva da semente para o fornecimento de nutrientes e energia para o desenvolvimento do eixo embrionário. A escolha da cultivar a ser utilizada é um dos principais fatores de sucesso para a cultura do milho (ARAÚJO & NASS, 2002), visto que existem genótipos que são adequados às diferentes condições climáticas brasileiras (EMBRAPA, 2012), podendo até, por exemplo, possuir tolerância ao déficit hídrico (PIMENTEL, 1999;CÂMARA et al, 2007), ao alagamento (ALVES et al, 2002) ou à incidência de algumas doenças (VON PINHO et al, 2001;SILVA et al, 2002).…”
Section: Introductionunclassified
“…Ainda segundo esses autores, o oxigênio é também fator fundamental para o processo germinativo, pois participa da degradação das substâncias de reserva da semente para o fornecimento de nutrientes e energia para o desenvolvimento do eixo embrionário. A escolha da cultivar a ser utilizada é um dos principais fatores de sucesso para a cultura do milho (ARAÚJO & NASS, 2002), visto que existem genótipos que são adequados às diferentes condições climáticas brasileiras (EMBRAPA, 2012), podendo até, por exemplo, possuir tolerância ao déficit hídrico (PIMENTEL, 1999;CÂMARA et al, 2007), ao alagamento (ALVES et al, 2002) ou à incidência de algumas doenças (VON PINHO et al, 2001;SILVA et al, 2002).…”
Section: Introductionunclassified
“…For the other traits, V g was the main fraction of the phenotypic variance (V p ), indicating that the observed differences are from genetic nature. In plant breeding, it is fundamental to obtain estimates of genetic parameters, allowing to identify the gene action nature involved in the control of the quantitative traits and to evaluate the efficiency of different breeding strategies to obtain genetic gains and to maintain adequate genetic basis in populations (Câmara et al, 2007). Cruz et al (2012) mention that when the adopted statistical model considers the genotypes as fixed effect, such as in the present study, the heritability passes to be denominated genotypic coefficient of determination (R 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Edwards (2011) reports that the selection for reducing the number of branches, the lower leaf angle and synchrony between male and female flowering, contribute to the increase in grain yield. In the same context, Câmara et al (2007) reported that the breeding programs for tolerance to abiotic stresses regard for character selection purposes as the number of branches, the period between the male and female flowering, prolificacy and delayed senescence of leaves (stay green).…”
Section: Resultsmentioning
confidence: 99%